2018
DOI: 10.21014/acta_imeko.v7i2.444
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol content determination in hard liquor drinks, beers, and wines, using a catalytic fuel cell. Comparison with other two conventional enzymatic biosensors: correlation and statistical data

Abstract: A catalytic fuel cell has been employed to check ethanol content in several samples of commercial wines, beers and hard liquor drinks. Two other conventional biosensors, based on catalase or alcohol oxidase enzyme, were also used, to the same purpose, on the same samples. Data obtained by three sensor methods have been compared and correlated. Lastly t-test and F-test were applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The present research can be considered as belonging to the research field reported in the literature concerning the development of fuel cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] and biofuel cells [ 28 , 54 , 55 , 56 , 57 ] for several purposes. This study positively extended applications to several pharmaceutical products (dyes) by a simple DMFC catalytic device (already performed on several alcoholic beverage samples [ 25 , 26 ]). The application to test the ethanol content of denaturated alcohol failed.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…The present research can be considered as belonging to the research field reported in the literature concerning the development of fuel cells [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] and biofuel cells [ 28 , 54 , 55 , 56 , 57 ] for several purposes. This study positively extended applications to several pharmaceutical products (dyes) by a simple DMFC catalytic device (already performed on several alcoholic beverage samples [ 25 , 26 ]). The application to test the ethanol content of denaturated alcohol failed.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, in this research, it was firstly demonstrated that the fuel cell can be useful to determine the ethanol content in several relevant pharmaceutical formulations, as dyes, with sufficient precision, accuracy, and robustness; secondly it was demonstrated that the enzymatic device can be also utilized to test other particular more complex organic molecules of pharmaceutical interest, such as the antibiotic imipenem; lastly, it was demonstrated that the enzymatic fuel cell seems to be useful for certain analytical forensic purposes, i.e., the measurement of ethanol in saliva and serum. In conclusion, owing to the low cost, the very low encumbrance of the cell and of the measurement system [ 25 ], and the high sensitivity and the short response time, achieved by adding enzyme alcohol dehydrogenase to the anodic section, this small enzymatic DMFC device [ 27 ] can be proposed as a suitable tool for several simple and fast analytical tests to be easy applied also in situ, with a few additional precautions [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before the current measurements, the Emstat automatically measured the open circuit voltage (OCV) value for a time of about 200 s, and then, the anode potential was set to a value of the optimized applied potential (OAP = OCV−100 mV) [ 25 , 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%